A Markovian Analysis of the Life of Newspaper Subscriptions - Deming, W. Edwards; Glasser, Gerald J. (Management Science, 1968)
This paper presents a case study in the application of some statistical theory, and a mathematical model, to an actual business problem. The problem was to determine the pattern of mortality of subscriptions to a daily newspaper, and thereby to ascertain the average life of such subscriptions. The method of solution, here with indicated, involved the collection of data from a probability sample of subscribers to the newspaper, and use of these data to construct a Markov chain.